Navigating Paul : an introduction to key theological concepts - Bassler, Jouette M. (Louisville, Ky. Westminster John Knox Press, 2007)
Jouette Bassler, one of the foremost experts on Pauline theology, offers her wisdom and insight into the core of Paul's thought in this brief and accessible book. She focuses on major themes in Paul, such as grace, law, faith, righteousness,Israel, resurrection, and what it means to be "in Christ." Through each of these themes, she explores...
Keywords: Bible. -- Epistles of Paul -- Theology. Bible. -- Epistles of Paul - Theology. Bible. -- Epistles of Paul